Implementation of Interpersonal Skills in Enhancing Interaction with Peers - Ulni Sapita; Juli Andriyani; Rizka Heni (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Interpersonal skills are important competencies that support effective communication and social interaction among university students. Although they can develop naturally through social experiences, many students still face difficulties in applying them in their daily interactions with peers. This study aims to analyze the implementation of interpersonal skills in enhancing peer interaction and to identify the challenges faced by students of the Islamic Guidance and Counseling Program, Faculty of Da'wah and Communication, UIN Ar-Raniry. The research employed a qualitative descriptive approach. Data were collected through observations and interviews with four purposively selected informants. Data analysis was conducted through three stages: data reduction, data display, and conclusion drawing. The findings show that interpersonal skills play an important role in improving the quality of peer interaction through openness, empathy, cooperation, tolerance, social responsibility, and effective communication. These skills help students build positive relationships, reduce misunderstandings, and strengthen cooperation. However, students still face obstacles such as difficulties in expressing opinions, initiating conversations, accepting differing viewpoints, and providing constructive criticism. Therefore, strengthening interpersonal skills needs to be carried out through practical training, simulations, and habituation of group work.